Development of Augmented Reality-Based Learning Media on Earth’s Rotation and Revolution Material for Sixth Grade Elementary Students - Choirun Nisa, Lidya; Anggoro, Subuh; Masanori, Fukui (Journal of Science Education Research, 2025)
This study aims to develop augmented reality-based learning media using the Assemblr EDU platform to help sixth-grade elementary school students understand the material on the rotation and revolution of the Earth. This research was conducted based on the background of high levels of misconceptions and misunderstandings among students, as well as the limited availability of learning media capable of visualising abstract concepts in the material on Earth's rotation and revolution. The research method used was Research and Development (R&D) with the Four-D development model (Define, Design, Develop, and Disseminate). The subjects of this study were 1 subject matter expert, 1 media expert, and 1 language expert, as well as 37 sixth-grade students and sixth-grade teachers at SDN 2 Sokaraja Kulon. Data collection techniques included surveys, direct interviews, validation questionnaires, and student and teacher response questionnaires. The product developed was an interactive learning medium with 3D visualisation and simulation animations, accompanied by a guidebook and markers. The media was validated and revised based on expert input, then tested on a small and large scale. The research results showed that the media was highly suitable and practical for use based on validity and practicality tests, with expert subject matter validation scores of 85%, expert media validation scores of 92.5%, expert language validation scores of 95%, student response rates of 99.63%, and teacher response rates of 98.75%. This media has proven effective in helping students understand the material on Earth's rotation and revolution, while also increasing student participation, interest, and enthusiasm.